2018
DOI: 10.5296/ijld.v8i2.13007
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Barriers and Leadership Conflicts Experienced by the Women in Higher Education in Saudi Arabia

Abstract: Based on the published scholarly works, this paper attempts to explore and accumulate the challenges and barriers that Saudi women leaders in higher education are experiencing in their professional lives.  For this purpose, literature review method has been adopted. Relevant scholarly articles published in 2004 to 2017 have been rigorously studied and cited. Findings of this paper suggest that women leaders in higher education generally experience assorted challenges, such as 1) socio-cultural, 2) organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…Furthermore, it is not an easy road for those who struggle to become leaders (Hodges, 2017). There is another misconception that women can only occupy and maintain a leadership position when they embody men's characteristics (Alsubhi et al, 2018). The stereotype and gender discrimination prevail on a larger scale (Varshney, 2019) and many believe that women must be relationship-oriented, lovely, friendly, and in charge of children.…”
Section: Cultural Barriersmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, it is not an easy road for those who struggle to become leaders (Hodges, 2017). There is another misconception that women can only occupy and maintain a leadership position when they embody men's characteristics (Alsubhi et al, 2018). The stereotype and gender discrimination prevail on a larger scale (Varshney, 2019) and many believe that women must be relationship-oriented, lovely, friendly, and in charge of children.…”
Section: Cultural Barriersmentioning
confidence: 99%
“…The stereotype and gender discrimination prevail on a larger scale (Varshney, 2019) and many believe that women must be relationship-oriented, lovely, friendly, and in charge of children. This perspective does not consider that women have the skills and capabilities for leading roles in many cases (Alsubhi et al, 2018). These stereotypes had an impact on women making them more careful about accessing leadership positions due to reputation fear drives (Hodges, 2017).…”
Section: Cultural Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…Many societies promote equal opportunities for women in the workforce, there are often societal values and deeply held cultural schemas that affect women's career and leadership development in organizations (Mate et al, 2018). Women experience assorted challenges, such as sociocultural, organizational, economical and personal and barriers faced including difficulty in work life balance, family responsibility, gender stereotype, gender roles in the socio-cultural practices, bureaucracy and gender inequality (Alsubhi, 2018). Few studies list few strategies adopted to overcome these barriers and those studies revealed how these strategies is helpful to women leaders to achieve successful leadership position (Rahaman and Mizanur, 2018 197 samples required for each cluster based on the target population of the study.…”
Section: Socio -Psychological Barriers and Strategiesmentioning
confidence: 99%